Design and Analysis of Compact Dual Band U-Slot Microstrip Patch Antenna with Defected Ground Structure for Wireless Application - Leo Pauline, S; R Ganesh Babu, T (International Journal of Engineering and Technology, 2018)
This paper explore aboutÂ Â the micro strip patch antenna design with a defected ground structure (DGS) for dual band operation. The intend of this paper is to design an micro strip antenna, under the frequency at 2.4 GHz and 5.2 GHz that can be utilized for BLUETOOTH and WLAN applications. The feeding technique used here is coaxial feed technique. The above said double band property can be established by etching U-slot in the ground plane. Being periodic structure slot is selected and it is imposed on ground plane. The periodic structures naturally modify the method of propagation of the electromagnetic signal passing on to the antenna. Essentially its core is to vary the parasitic capacitance and inductance of the material through which the substrate is made. This may moreover leads to the reduction in size and progress the performance of the antenna. Micro strip patch antennae are favored due to the fact that these are small in size, inexpensive, consume low power and easy to fabricate and also be designed to meet wide band application requirements.Â Â